ANALISIS MAKNA NASIONALISME DALAM FILM 3 SRIKANDI - Lopiana Kristina M. M.; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The young generation as the successor to the ideals of the nation have hobbies and talents as well as achievements that must be developed for the achievement of intellectual and quality human resources. can give birth to strong cadres to achieve the national goals of the nation, in order to strengthen brotherhood, strengthen national unity. The purpose of this study is to find out the meaning of nationalism at the reality level, the level of representation and the level of ideology in the 3 Srikandi film.               This study uses a qualitative method with an approach that is analyzed by Jhon Fiske's semiotic analysis The subjects and objects in this study were observations of audio and visual displays in scenes from the 3 Srikandi film with data collection techniques used were observation, documentation, and literature study.               The results of this study indicate there is an Analysis of the Meaning of Nationalism in the film 3 Heroine. Analysis of the Meaning of Srikandi 3 film nationalism seen from three levels proposed by John Fiske, namely: at the level of reality, Analysis of the Meaning of Nationalism In the film 3 Srikandi looks at aspects of appearance, manner of speech, behavior, gestures, expressions and environment. At the level of representation, the technical and conventional codes contained in the 3 Srikandi film which depicts the Analysis of the Meaning of Nationalism in the 3 Srikandi film are reflected through aspects of the camera, lighting, music and sound. The level of ideology that can be concluded, the depiction of the values of nationalism so that the ideology inferred is the ideology of patriarchy and feminism.